Improving antitumor targeting via using PL3 homing peptide and cell-penetrating peptide Authors - Dhafir Masheta; Shafq Al-Azzawi (Research Results in Pharmacology, 2023)
Introduction: Tumor-homing peptides have gained great attention as tools for the development of non-invasive and targeting drug delivery systems (DDS) to minimize drug systemic toxicity and enhance bioavailability. This study aims to improve antitumor targeting in prostate cancer via uploading a drug to a DDS comprised of a cell penetrating peptide decorated with a tumor-homing peptide, PL3.